Situation Report: Hungary, 1 August 1979 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe/Radio Liberty based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Major Consumer Price Increases Deputy Prime Minister Istvan Huszar's Comment on Price Increases What People Are Earning Price Increases despite Hog and Poultry Glut Romanian Prime Minister's Official Friendly Visit Khrushchev: The First Man in Space - Or So Some Young Hungarians Think Applications and Admissions to Institutions of Higher Education Quest for Dollars Changes Target Countries for Cattle Exports